Critical analysis of the transmission systems expansion planning problem considering multiple generation scenarios - Freitas, Patricia F. S. [UNESP]; Romero, Ruben [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
In a competitive electric market environment, it is important to develop an expansion plan for transmission systems that is capable of dealing with the needs of the market. In addition, the uncertainties in generation and demand must be taken into account when elaborating these expansion plans. One way of considering these facts is to expand the transmission system considering a set of generation scenarios that adequately represent uncertainties and competitive market requirements. In this context, the transmission systems expansion planning problem considering multiple generation scenarios (MGS) appears. In this case, the costs of expansion grow prohibitively. Therefore, this paper presents a strategy to find expansion plans for this problem with lower costs. The strategy chooses a small generation range as opposed to choosing a generation point for each generating bus. The linear disjunctive formulation is used model the problem and the IEEE 24-bus system is used to perform the tests. The obtained result presents lower investment costs when compared to the traditional mathematical model for transmission systems expansion planning considering MGS.
Keywords: Expansion planning; Linear disjunctive model; Multiple scenarios; Transmission systems